Development of SSR markers by 454 sequencing in the endemic species Gentianella praecox subsp. bohemica (Gentianaceae) - Šurinová, Mária; Brabec, Jiří; Münzbergová, Zuzana (Applications in plant sciences, 2017)
PREMISE OF THE STUDY: Polymorphic microsatellite loci were developed and used to genotype individuals of Gentianella praecox subsp. bohemica (Gentianaceae), a highly protected taxon in Europe, to study the genetic structure of the remaining populations. METHODS AND RESULTS: Thirty-eight primer pairs were successfully amplified; of these, 12 polymorphic microsatellite loci were developed using a 454 sequencing approach and used to genotype 180 individuals of G. praecox subsp. bohemica from six populations. Allelic richness ranged between one and nine alleles per locus. We detected a high frequency of polyploid individuals (77.8%). The highest average percentage of heterozygous genotypes was identified for samples from the Hroby population (75.5%). All loci can also be amplified in the congeneric species G. praecox subsp. praecox, G. amarella subsp. amarella, and G. obtusifolia subsp. sturmiana. CONCLUSIONS: These markers will provide knowledge on patterns of gene flow and population genetic structure, which is necessary for current protection actions and for effective conservation of this species in the future.
Keywords: Gentianaceae; genotyping; microsatellites; Gentianella praecox subsp. bohemica; polyploidy